Cellular processing of bovine factors X and Xa by cultured bovine aortic endothelial cells (The Rockefeller University Press, 1985)
Previous studies have shown that Factor X and Factor Xa bind specifically to distinct sites on the endothelial cell surface. Since the coagulant activity of a cell-bound clotting protein is dependent on its remaining on the cell surface, endocytosis and degradation studies have been carried out. Cell-bound Factor X was internalized at 0.07 fmol/min/10(6) cells, a rate slower than its dissociation from the cell surface. Endocytosed Factor X was not degraded, but was returned to the cell surface. In contrast, Factor Xa was internalized at an initial rate of 0.38 fmol/min/10(6) cells and subsequently degraded at about the same rate. The degradation of Factor Xa was prevented by chloroquine. These results suggest that Factor Xa is internalized and degraded by a lysosomal-dependent pathway. Studies with Factor X- and Xa-colloidal gold conjugates showed endocytosis proceeding at coated pit regions, and accumulation of Factor Xa-gold particles in lysosome- like structures. Endocytosis was studied as a clearance pathway for cell-bound Factor Xa by activating Factor X with Factors IXa and VIII on the endothelial cell surface. Endocytosis of the Factor Xa formed was significant, as only 44% of the Factor Xa formed was released into the supernatant, whereas the remainder was internalized and degraded. Thus, endocytosis of Factor Xa bound to its specific endothelial cell sites may be an important factor in the balance of vessel wall hemostatic mechanisms.